Simulasi Pengaruh Kombinasi Target-Filter Tambahan Terhadap Spektrum Sinar-X pada Tabung Pesawat Mammografi dengan Program EGSnrc - Budiwati, Trisna; Anam, Choirul; Setiawati, Evi (JURNAL SAINS DAN MATEMATIKA, 2011)
The mammography use the specific x-ray energy. At high x-ray energies (>35 keV) the subject contrast between the normal and malignant tissues in the breast is poor, at very low x-ray energies (10-15 keV) the contrast is highest, however the high absorption result in a high tissue dose. To achieve to good result must be used the optimal energy, that could be achieved by using specific x-ray target and additional filter materials to generate characteristic x-ray of the desired energy. This research was aimed to evaluate the influence of target-additional filter combination and filter thickness to the x-ray energy spectrum. The research was conducted by Monte Carlo simulation using EGSnrc program. The model of mammography tube was designed by BEAMnrc program, and phase space file was resulted by BEAMnrc was analyzed by BEAMDP. The tube x-ray contained of target and additional filter from molybdenum (Mo) and rhodium (Rh) material, window from berrylium, and collimator from Pb. Target-additional filter combination were Mo-Mo, Mo-Rh, Rh-Rh and Rh-Mo.Â  Variation of additional filter thickness that be used are 0,001 mm; 0,03 mm; and 0,05 mm. The results of the simulation indicated that an x-ray consist of bremmstrahlung and characteristic. X-ray spectrum were produced by Mo target had characteristic x-ray energy 17 keV and 19 keV, and Rh target had characteristic energy 20 keV and 23 keV. Target-additional filter combination that allowed are Mo-Mo, Mo-Rh, and Rh-Rh combination. Rh-Mo combination could not be used, because Mo filter would attenuated x-ray characteristic energy. For the Mo-Mo and Rh-Rh, the thicker the additional filter then the x-ray spectrum obtained has a more narrow, but the reduced intensity of the x-ray bremmstrahlung and characteristic. Â  Keywords: target-filter combination, x-ray spectrum, mammography, EGSnrc.